Oral Health, Oral Microbiota, and Incidence of Stroke-Associated Pneumonia—A Prospective Observational Study - Cieplik, Fabian; Wiedenhofer, Alma Maria; Pietsch, Verena; Hiller, Karl-Anton; Hiergeist, Andreas; Wagner, Andrea; Baldaranov, Dobri; Linker, Ralf A.; Jantsch, Jonathan; Buchalla, Wolfgang; Schlachetzki, Felix; Gessner, André (Frontiers in Neurology, 2020)
Stroke-associated pneumonia is a major cause for poor outcomes in the post-acute phase after stroke. Several studies have suggested potential links between neglected oral health and pneumonia. Therefore, the aim of this prospective observational study was to investigate oral health and microbiota and incidence of pneumonia in patients consecutively admitted to a Stroke Unit with stroke-like symptoms. This study involved three investigation timepoints. The baseline investigation (within 24 h of admission) involved collection of demographic, neurological and immunological data, dental examinations and microbiological sampling (saliva, subgingival plaque). Further investigation timepoints 48 h or 120 h after baseline included collection of immunological data and microbiological sampling. Microbiological samples were analyzed by culture technique and by 16S rRNA amplicon sequencing. From the 99 patients included in this study, 57 were diagnosed with stroke and 42 were so-called stroke-mimics. From 57 stroke-patients, 8 (14%) developed pneumonia. Stroke-associated pneumonia was significantly associated with higher age, dysphagia, greater stroke severity, embolectomy, nasogastric tubes and higher baseline-CRP. There were trends towards higher incidence of pneumonia in patients with more missing teeth and worse oral hygiene. Microbiological analyses showed no relevant differences regarding microbial composition between the groups. However, there was a significant ecological shift over time in the pneumonia patients, probably due to antibiotic treatment. This prospective observational study investigating associations between neglected oral health and incidence of SAP encourages investigations in larger patient-cohorts and implementation of oral hygiene programs in Stroke Units that may help reducing incidence of stroke-associated pneumonia.